Animal models of human atherosclerosis: current progress - Poznyak, A.V. (Braz J Med Biol Res, 2020)
Atherosclerosis retains the leading position among the causes of global morbidity and mortality worldwide, especially in the industrialized countries. Despite the continuing efforts to investigate disease pathogenesis and find the potential points of effective therapeutic intervention, our understanding of atherosclerosis mechanisms remains limited. This is partly due to the multifactorial nature of the disease pathogenesis, when several factors so different as altered lipid metabolism, increased oxidative stress, and chronic inflammation act together leading to the formation and progression of atherosclerotic plaques. Adequate animal models are currently indispensable for studying these processes and searching for novel therapies. Animal models based on rodents, such as mice and rats, and rabbits represent important tools for studying atherosclerosis. Currently, genetically modified animals allow for previously unknown possibilities in modelling the disease and its most relevant aspects. In this review, we describe the recent progress made in creating such models and discuss the most important findings obtained with them to date.